Caregivers’ perceptions of feeding practices and diet diversity among children aged 12–59 months in a rural district of South India: an analytical cross-sectional study - George, Neethu; George, Meera; Dharmaraj, Rock Britto; Rangasamy, Madeshwaran Chitra; Gandhi, Kaviya; Mahadeavan, Lenin; Dhanasekaran, Kowsika Suveda; Venkatachalam, Keerthanaa; Ramesh, Madumitha; Subbhaiyaa, Muthu Raaj Kumar Rukmani (British Medical Journal Publishing Group, 2024)
Objective The primary objective of this study was to assess caregivers’ perceptions of feeding practices (breastfeeding and complementary feeding) and diet diversity among children aged 12–59 months in a rural district of South India. The secondary objective was to identify potential predictors of these perceptions and diet diversity. Design An analytical cross-sectional study was performed from March 2023 to May 2023. Setting In a rural district of Tamil Nadu, South India. Participants This study included 301 mothers/caregivers of children between 12 and 59 months of age in a rural district of Tamil Nadu. The research gathered demographic information from caregivers, including details such as age, educational background, occupation, relationship with the child and place of residence. Additionally, the caregivers’ perspectives were evaluated through a questionnaire focused on breastfeeding/complementary feeding, and the diet diversity of the children was also assessed. Outcome measures The primary outcome was the perceptions of mothers/caregivers of children between 12 and 59 months of age about breastfeeding/complementary feeding practices, and the diet diversity of the children was measured. Additionally, predictors associated with these perceptions were evaluated through regression analysis. Results In the present study, 188 (62.5%) and 179 (59.5%) of the participants had good perceptions of breastfeeding practices and complementary feeding practices, respectively. This binomial regression revealed that subjects with unstable occupations (adjusted OR=2.24, 95% CI 1.25 to 4.01), schooling (7.71, 95% CI 2.73 to 8.9) and higher education (38.32, 95% CI 4.63 to 316.85) had increased chances of having good perceptions of breastfeeding practices. Subjects with unstable occupations (0.23, 95% CI 0.06 to 0.85), stable occupations (0.13, 95% CI 0.04 to 0.51), schooling (0.43, 95% CI 0.25 to 0.74), higher education (0.15, 95% CI 0.04 to 0.50) and increased birth weights (2.54, 95% CI 1.35 to 4.78) had increased chances of having good perceptions of complementary feeding practices (p<0.05). This study revealed that 86.4% of the children had adequate diet diversity. Conclusion The study revealed that most caregivers, particularly mothers, possess a strong understanding of breastfeeding and complementary feeding practices, with education and occupation exerting a notable influence. However, there is a crucial necessity to translate this knowledge into practical applications to effectively obtain feeding indicators.